A New Species of the Genus Tephritis (Diptera, Tephritidae) from Turkmenistan, Kazakhstan, and Iran - Korneyev, S.V.; Mohamadzade Namin, S. (Вестник зоологии, 2013)
Tephritis tridentata S. Korneyev and Mohamadzade Namin, sp. n. reared from the flower heads of Jurinea baissunensis Iljin in South-Eastern Kazakhstan, Western Turkmenistan and Southern Iran is described. It is similar to T. bardanae Schrank, T. dilacerata Loew, T. formosa Loew, T. kovalevi V. Korneyev et Kameneva, T. valida Loew and T. zernyi Hering in the widely brown wing pattern with two dark spots at apices of veins R4+5 and M (instead of apical fork) and three spots (two large hyaline and one small yellowish ) in cell r1, differing from all known species by having three brown bar-like crossbands in the posterior half of the wing (diffusely spotted in compared species).